2020
DOI: 10.1016/j.ejmech.2020.112402
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of thiourea-based derivatives as Mycobacterium tuberculosis growth and enoyl acyl carrier protein reductase (InhA) inhibitors

Abstract: Tuberculosis remains the most deadly infectious disease worldwide due to the emergence of drug-resistant strains of Mycobacterium tuberculosis. Hence, there is a great need for more efficient treatment regimens. Herein, we carried out rational molecular modifications on the chemical structure of the urea-based co-crystallized ligand of enoyl acyl carrier protein reductase (InhA) (PDB code:5OIL). Although this compound fulfills all structural requirements to interact with InhA, it does not inhibit the enzyme ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The most promising compound (18, Figure 7) displayed a 2.6-log reduction in bacterial count. Activity against active bacilli and M.tb in infected macrophages was also confirmed [175].…”
Section: Other Targetsmentioning
confidence: 70%
“…The most promising compound (18, Figure 7) displayed a 2.6-log reduction in bacterial count. Activity against active bacilli and M.tb in infected macrophages was also confirmed [175].…”
Section: Other Targetsmentioning
confidence: 70%
“…In general, PTUs were 5-10-fold more active against intracellular bacteria. To the best of our knowledge, this is the first report of these compounds as antitubercular agents although other thiourea derivatives have antitubercular activity(2124).…”
Section: Resultsmentioning
confidence: 90%
“…To the best of our knowledge, this is the first report of these compounds as antitubercular agents although other thiourea derivatives have antitubercular activity (21)(22)(23)(24).…”
Section: Extracellular (µM) Ic 90mentioning
confidence: 89%
See 1 more Smart Citation
“…The (thio)urea branch is an element of several medicines with anticancer profiles, such as sorafenib, multikinase-inhibitory diarylthiorea derivative, or tenovin-1, the benzylthiourea, which acts as a reversible inhibitor of class III HDAC sirtuins (Figure 1). On the other hand, it was reported that (hetero)aryl terminal fragments of thiourea moiety, enriched with electron-negative substituents, could provide biological responses, not only cytotoxic [2][3][4], but also antibacterial [2][3][4][5][6][7][8], antiviral [2,[9][10][11][12], antimycobacterial [5,13], antioxidant [14], and anti-inflammatory [6] properties, as well as central nervous system activation [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%